Liver metastasis seen in whole body I-131 Scintigraphy of post operated Patient with well differentiated papillary carcinoma - Yadav, Ajay Kumar; Ray, Raj Narayan; Joshi, Swechchha; Ansari, Quamrul Haque (Nepalese Journal of Cancer, 2017)
Well differentiated papillary carcinoma of thyroid metastasizes to regional lymph nodes and the patients usually present with cervical or mediastinal lymphadenopathy. In this case report, we found a case of papillary thyroid carcinoma with hepatic metastasis and also presence of lymph nodal metastasis which is very rare.